The cross, the plow and the skyline : contemporary science fiction and fantasy and the ecological imagination - Yanarella, Ernest J. (BrownWalker Press, 2022)
"The apocalyptic, pastoral, and urban traditions have fundamentally shaped Western history and influenced American religion, culture, and politics. This book argues that these traditions have not only been decisive in giving form and substance to classic and modern American literature, but have been appropriated by contemporary science fiction. As a loosely connected set of cultural narratives, the Cross, the Plow, and the Skyline have through the medium of science fiction provided a bold vista on the future grounded in an emergent ecological imagination"--